Fungal contamination of medical students’ mobile phones from the University of Belgrade, Serbia: a cross-sectional study - Eleonora Dubljanin; Teodora Crvenkov; Isidora Vujčić; Sandra Šipetić Grujičić; Jakša Dubljanin; Aleksandar Džamić (Scientific Reports, 2022)
Abstract The study aimed to characterize fungal contamination of medical students’ mobile phones, investigate mobile phones’ usage and cleaning habits, identify independent risk factors for fungal contamination, and awareness of mobile phones as a potential route of infection. In a cross-sectional study, medical students’ mobile phones were sampled for possible fungal contamination. The questionnaire was used to record mobile phone usage, cleaning habits, and awareness of mobile phones as a source of infection. A total of 492 medical students were included and fungal contamination of mobile phones was confirmed in 32.11%. The most frequent fungal isolates on students’ mobile phones were Candida albicans (28.5%), followed by Aspergillus niger (11.4%), and Penicillium chrysogenum (9.5%). Factors independently associated with fungal contamination of students’ mobile phones were: lack of mobile phone cleaning (OR = 0.381; p < 0.001), and usage of mobile phones near patients’ beds (OR = 0.571; p = 0.007). The results of this study confirmed that students who use their mobile phones in hospital wards have a higher rate of fungal contamination. The development of active surveillance and preventive strategies is needed to reduce the risk of cross-contamination and increase awareness of fungal transmission via mobile phones.